Constitutional Legislation Developments in the Russian Federation for Sustainable Development Goals - V. P. Kirilenko; G. V. Alekseev (Теоретическая и прикладная юриспруденция)
The improvement of constitutional legislation at the national level is impossible without taking into account the progressive transformations in the international system that predetermine progress in solving the political problems of our time. Democracy as a non-alternative political regime and the rule of law as the principle of social organization guarantee the legitimacy of decisions of the public authority of the state as long as the level of legal culture of the people allows you to remain within the legal framework, updating the interpretation of formal requirements of the constitutional law. The historical context of the modernization of the legal foundations of the state system affects legal awareness only to the extent that changes in the law give rise to progressive practices of human rights protection. Many ambitious political projects and current reforms have not been properly developed due to the fact that the practical results of the modernization of the constitutional system strongly contradicted the picture of social justice that formed the ideological basis for the humanitarian policy. Preserving legal traditions while updating the interpretation of the provisions of constitutional acts in the practice of constitutional justice can contribute to the achievement of sustainable development goals to a much greater extent than those changes in the text of constitutional acts that carry the risks of political instability and violation of human rights.